2012
DOI: 10.1254/jphs.11r11cp
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms for the Action of Chymase Inhibitors

Abstract: Abstract. Angiotensin II plays an important role in regulating blood pressure. Moreover, angiotensin II directly promotes organ damage by inducing expression of various genes, such as transforming growth factor (TGF)-β and matrix metalloproteinase (MMP)-9 precursors. Blockade of angiotensin II has been shown to not only lower blood pressure, but also to prevent cardiovascular and renal dysfunction and fibrosis. Inhibition of TGF-β and MMP-9 has also been shown to prevent cardiovascular and renal damage. A mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…Chymase is co-stored with heparin proteoglycan in the secretory granules of mast cells. Chymase is dispersed from the mast cells immediately after mast cell degranulation, and the activity of dispersed chymase into interstitial tissues is maintained several days after degranulation [28]. Therefore, in the present study, up-regulated chymase activity might have been observed from 1 h until 24 h after LPS/GalN injection.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Chymase is co-stored with heparin proteoglycan in the secretory granules of mast cells. Chymase is dispersed from the mast cells immediately after mast cell degranulation, and the activity of dispersed chymase into interstitial tissues is maintained several days after degranulation [28]. Therefore, in the present study, up-regulated chymase activity might have been observed from 1 h until 24 h after LPS/GalN injection.…”
Section: Discussionmentioning
confidence: 66%
“…The other specific chymase inhibitor, NK3201, has also shown MMP-9 inhibitory effects in various disease models [25,26,27]. Although chymase inhibitors cannot directly inhibit MMP-9 activity, chymase inhibition may be useful for the reduction of MMP-9 activity via prevention of the conversion of MMP-9 from pro-MMP-9 [28]. Thus, the attenuation of hepatic MMP-9 activity by TY-51469 might contribute to reducing the symptoms of ALF after LPS/GalN injection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, diabetes mellitus may present inhibition of mast cell activation, a decrease of leukocyte-endothelial cell interactions, reduced numbers of leukocytes in inflammatory sites, a decrease of microvascular responses to inflammatory compounds, including histamine, a reduction in protein loss, and a decrease of acute inflammatory reactions [80].…”
Section: Type 2 Diabetes Mellitus and Mast Cellsmentioning
confidence: 99%
“…Therefore, inhibition of activated MCs and their degranulation and/or inflammatory cytokine/chemokine generation might act to protect pancreatic β cells in T1DM [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we postulate that the primary effect of doxycycline is based on its inhibition of mitochondrial protein synthesis, preventing clonal expansion of T-cells and possibly also other proliferating cells in AAA tissue, thus, indirectly, resulting in a decrease of proinflammatory cytokines, MMP-2 and MMP-9 that otherwise damage the vascular stroma [9,28,41]. Whilst there is no direct experimental evidence available that the observed effects of doxycycline on AAA are based on its inhibition of mitochondrial protein synthesis, the finding of Lu et al [11] that aneurysmal lesions contain clonally expanded T cells combined with our own observations in cancer research that doxycycline results in a proliferation arrests of T cells through its inhibition of mitochondrial protein synthesis [72,73] lends strong support to our hypothesis.…”
Section: Direct and Indirect Effects Of Doxycyclinementioning
confidence: 99%